PEMODELAN 3D STRUKTUR BAWAH PERMUKAAN GUNUNGAPI AGUNG PROVINSI BALI MENGGUNAKAN METODE GAYA BERAT - Nasyratul Ilmi; Karyanto Karyanto (Engineering Faculty Universitas Lampung, 2019)
Under surface structure, 3d modelling of Agung volcano in Bali had been conducted by using gravity methods. This research aims to identify the magma chamber and make a model below the surface of the Great Volcano of Bali Province by using gravity anomaly data. Data processing methods performed in this research were consists of six steps: (i) arrangement the contour map of Bouguer anomaly, (ii) spectrum analysis, (iii) anomaly regional and residual separation, (iv) Second Vertical Derivative analysis, (v) cross-section of subsurface geology construction by using 3D (inverse modelling), (vi) qualitative and quantitative interpretation. Anomaly Bougeur contour map result shows the value of Bouguer anomaly in research area around 84 mGal spreading around west-south part of research point until 279 mGal on Agung volcano body. Anomaly regional value is around 97 mGal to 253 mGal. The boundary between basement a sedimentary rock of the research area are at the depth of 0,89 km. The magma chamber of Agung volcano is in the depth of 500 to 8000 metres to a form of towing up and polluted in the middle. The density of the magma chamber is around 2,73 until 2,86 gr/cc. The magma flow in the Agung volcano of visible at the depth of 0 metres.